2011
DOI: 10.1080/10426911003636910
|View full text |Cite
|
Sign up to set email alerts
|

Grain Size Effect in the Micro-V-Bending Process of Thin Metal Sheets

Abstract: The aim of this study is to develop a micro-V-bending testing system and to investigate the grain size effect of 99.5% Ferrum sheet plate in the micro-V-bending process. In this study, two experiments have been conducted. They attempt to explain the characteristic of thickness variation at a constant average grain size of 29.93 m with a standard deviation (SD) of 2.4 and the different average grain sizes at a constant mean thickness of 490.63 m with a SD of 11.3. A laser displacement sensor is employed to moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 13 publications
(14 reference statements)
0
16
1
Order By: Relevance
“…This indicates that the grain size effect obviously affects the flow stress of this kind of material. In addition, some prior researches also verified the grain size effect in the copper [25], C2680 brass [23], CuZn37 brass [19], Fe [26], et al…”
Section: Effect Of Grain Size On Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the grain size effect obviously affects the flow stress of this kind of material. In addition, some prior researches also verified the grain size effect in the copper [25], C2680 brass [23], CuZn37 brass [19], Fe [26], et al…”
Section: Effect Of Grain Size On Materials Propertiesmentioning
confidence: 99%
“…Chen and Jiang [26] adopted T/D ratio to investigate the springback behavior in micro V-bending test and found that for the constant grain size, the springback angle decreases with an increase in T/D ratio. For the constant thickness, nevertheless, the springforward occurs when T/D ratio is less than 2, as shown in Fig.…”
Section: Effect Of Thickness To Grain Size Ratio On Springback Anglementioning
confidence: 99%
“…Besides, an increasing of elastic anisotropy of surface grains with the reduction of grains along the thickness direction will cause the springback angle scattering [4,5]. Chen et al [6] discovered that yield strength and maximum punch force decrease with a decrease of t/d ratio. It was also found that when the t/d ratio is smaller than 2, spring-forward occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [11,16,18] have proved that the ratio T/D is a wide-applied indicator evaluation parameter for studying the relationship between the the grain size effect and springback. However, it is also found that there is a lack of research on grain size effect when the ratio is around 1 (greater than 1, less than 1 and equal to 1).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [16] conducted micro V-bending with different T/D ratios' ferrum specimens and discussed the relationship between the T/D and bending behaviours. Similarly, Wang et al [17] investigated the grain size effect on springback in micro U-bending.…”
Section: Introductionmentioning
confidence: 99%